Generation of a transgene-free Induced pluripotent stem (iPS) cell line (JNCHi002-A) from a female heterozygous carrier of the low density lipoprotein receptor (LDLR) gene mutation (c.387delC) - Rujin Tian; Yixiao Li; Hongmei Xin; Yue Jiang; Haozheng Zhang; Lin Zhong; Zhongtao Gai; Qianqian Deng; Chunhui Wang; Kaihui Zhang (Stem Cell Research)
The low density lipoprotein receptor （LDLR) gene (OMIM#606945)encodes a protein of 860 amino acids. The encoded protein typically anchors itself to the cell membrane, where it facilitates the binding and internalization of low-density lipoprotein/cholesterol into the cell. Once inside, lysosomes liberate the cholesterol, which then becomes available to suppress the activity of the microsomal enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. This enzyme serves as the rate-limiting step in the biosynthesis of cholesterol. We generated a human iPS cell line from a 38-years-old woman carrying a heterozygous mutation (c.387delC) in LDLR gene. This cell line retains the original mutation site and shows differentiation potential towards three germ layers in vitro, which can be used as a disease model for research.